Molecular dynamics simulations of Ibuprofen release from pH-gated silica nanochannels - Rodriguez, Javier (2015)
The iboprufen delivery process from cylindrical silica pores of diameter 3~nm, with polyamine chains anchored at the pore outlets, was investigated by means of massive molecular dynamics simulations. Effects from pH were introduced by considering polyamine chains with different degree of protonation. High, low and intermediate pH environments were investigated. The increment of the acidity of the environment leads to a significant decrease of the pore aperture,  yielding an effective diameter, for the lowest pH case, that is 3.5~times smaller than the one associated to the highest pH one. Using a biased sampling procedure, Gibbs free energy profiles for the ibuprofen delivery process were obtained. The joint analysis of the corresponding profiles, time evolution of the ibuprofen position within the channel, orientation of the molecule and instantaneous effective diameter of the gate, suggests a 3-steps mechanism for ibuprofen delivery. A complementary analysis of the translational mobility of ibuprofen along the axial direction of the channel revealed a sub-diffusive dynamics in the low and intermediate pH cases. Deviations from Brownian diffusive dynamics are discussed and compared with direct experimental results.